2017
DOI: 10.1080/09712119.2017.1284073
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary formic acid on the in vitro ruminal fermentation parameters of barley-based concentrated mix feed of beef cattle

Abstract: Baytok (2018) Effect of dietary formic acid on the invitro ruminal fermentation parameters of barley-based concentrated mix feed of beef cattle,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Methane production was positively correlated with the OMD, NH 3 -N, numbers of microorganisms in the rumen, total VFA concentration and the (A + B) : P ratio. In agreement with our fermentation results, previous studies have reported Holotrich protozoa to be important for methanogenesis in the rumen (Belanche et al 2012;Belanche et al 2015;Kara et al 2018).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Methane production was positively correlated with the OMD, NH 3 -N, numbers of microorganisms in the rumen, total VFA concentration and the (A + B) : P ratio. In agreement with our fermentation results, previous studies have reported Holotrich protozoa to be important for methanogenesis in the rumen (Belanche et al 2012;Belanche et al 2015;Kara et al 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Non-fibrous carbohydrate contents (NFC) were calculated using NDF, CP, EE and ash values (NRC 2001). The chemical composition and ingredients of the concentrated mix feed for beef cattle is presented in Table 1 (Kara et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The amount was somewhat higher for the potato group, but this was probably not a major factor affecting the outcomes of the experiment. Kara et al [31] reported that no significant differences were observed between 4 and 8 mL of formic acid/kg of TMR on ruminal fermentation parameters. Additionally, based on the recommendation from EFSA [32], the formic acid supply to cows was lower than the maximum proposed dose (10,000 mg (8.2 mL) of formic acid/kg of TMR).…”
Section: Dairy Cows Fed Potato By-product (Experiments 1)mentioning
confidence: 97%
“…We collected data from dissertations, theses, and scientific articles published by Lima (2016), Becker (2015), Cieślak et al (2006), Rodrigues (2017), Benetel (2018), Araujo (2010), Souza (2014), Kara et al (2016), Kara et al (2018), Ramirez-Bribiesca et al (2018, Ugwuowo et al (2017), Mallmann (2013, Medjekal et al (2018), Nguluve (2014), Rivera (2006), Molina-Alcaide et al (2017) and Garcia (2013).…”
Section: Data Set Descriptionmentioning
confidence: 99%
“…Rivera (2006), Molina-Alcaide et al (2017 and Garcia (2013) evaluated the additives in diets. The data set composed by Mallmann (2013), Kara et al (2018), Ramirez-Bribiesca et al (2018 and Ugwuowo et al (2017) were feedstuffrich in protein. CH4 production tends to increase when the diet contains forages with different phenological ages.…”
Section: Data Set Descriptionmentioning
confidence: 99%